Analysis Of The Learning Effectiveness Of Digital-Based Islamic Religious Education Courses At Muhammadiyah University Of Bengkulu - Zona Julita; Dedy Novriadi; Lety Febriana; Desi Firmasari (Yayasan Rahmat Islamiyah, 2026)
This study aims to describe the implementation of digital-based Islamic Religious Education (PAI) learning media in fifth-grade classes at SD Fatma Kenanga, Bengkulu City, to examine students’ learning motivation in participating in digital-based PAI learning, and to analyze the supporting and inhibiting factors affecting the use of digital learning media in enhancing students’ learning motivation. This research employed a qualitative descriptive method, with data collected through in-depth interviews with the PAI teacher, questionnaires distributed to 20 fifth-grade students, direct classroom observations, and analysis of findings linked to relevant learning theories. The results of the study indicate that the use of digital learning media, particularly educational videos, is still relatively limited in PAI instruction. This limitation is mainly due to the dominance of conventional teaching methods such as lectures, discussions, and the use of whiteboards and textbooks. However, when digital media were implemented, the learning process became more engaging and interactive, leading to increased student motivation, enthusiasm, active participation, and understanding of PAI materials, especially those related to worship practices and moral values. Based on the questionnaire results, only three out of twenty students showed a moderate level of learning motivation, while the majority demonstrated high to very high motivation levels. Inhibiting factors included limited internet access and restricted availability of facilities such as projectors and Chromebooks, which had to be shared among classes. Overall, digital-based PAI learning media were proven to be effective in enhancing students’ learning motivation and contributed significantly to the development of more innovative and contextual PAI learning strategies.